Retinoic Acid Induces Ubiquitination-Resistant RIP140/LSD1 Complex to Fine-Tune Pax6 Gene in Neuronal Differentiation. (9th October 2015) - Wu, Cheng-Ying; Persaud, Shawna D.; Wei, Li-Na
Abstract: Receptor-interacting protein 140 (RIP140) is a wide-spectrum coregulator for hormonal regulation of gene expression, but its activity in development/stem cell differentiation is unknown. Here, we identify RIP140 as an immediate retinoic acid (RA)-induced dual-function chaperone for LSD1 (lysine-specific demethylase 1). RIP140 protects LSD1's catalytic domain and antagonizes its Jade-2-mediated ubiquitination and degradation. In RA-induced neuronal differentiation, the increased RIP140/LSD1 complex is recruited by RA-elevated Pit-1 to specifically reduce H3K4me2 modification on the Pax6 promoter, thereby repressing RA-induction of Pax6 . This study reveals a new RA-induced gene repressive mechanism that modulates the abundance, enzyme quality, and recruitment of histone modifier LSD1 to neuronal regulator Pax6, which provides a homeostatic control for RA induction of neuronal differentiation.